2019
DOI: 10.1177/1742395319882069
|View full text |Cite
|
Sign up to set email alerts
|

Coping with diabetes stress among adults in rural Dominican Republic: “I don’t think about it”

Abstract: Objectives As type 2 diabetes prevalence increases across Latin America, understanding local approaches to coping with diabetes stress is essential to providing care that incorporates patients’ values and preferences. This study explored a local phenomenon, “ no le doy mente” (I don’t think about it), used by adults with type 2 diabetes in the Dominican Republic to cope with diabetes stress. Methods We conducted 19 qualitative in-depth interviews with adults with type 2 diabetes (10 men, 9 women) recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For instance, Stonbraker et al identified the same sentiment in a separate study conducted at the same research site in the Dominican Republic (Stonbraker, Arcia, et al, 2017). Sadeghzadeh et al, found that Dominican participants living with type 2 diabetes felt diabetes was worse than HIV because of the extensive lifestyle modifications that diabetes requires for successful management (Sadeghzadeh et al, 2021). PLWH living outside the Dominican Republic express this sentiment as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Stonbraker et al identified the same sentiment in a separate study conducted at the same research site in the Dominican Republic (Stonbraker, Arcia, et al, 2017). Sadeghzadeh et al, found that Dominican participants living with type 2 diabetes felt diabetes was worse than HIV because of the extensive lifestyle modifications that diabetes requires for successful management (Sadeghzadeh et al, 2021). PLWH living outside the Dominican Republic express this sentiment as well.…”
Section: Discussionmentioning
confidence: 99%
“…Identity reformation allows people to confront their initial fear and/or embarrassment regarding their diagnosis and establish a new sense of self that promotes function and disease management (Aryal, 2018;Ho & Goh, 2017;Laws, 2016). The presence of this transformation has been observed in other Dominican PLWH (Barrington et al, 2018) as well as Dominicans living with type 2 diabetes (Sadeghzadeh et al, 2021). How quickly individuals complete their transformation likely depends on individual factors such as their frame of mind, self-esteem, level of social and professional support, and/or their level of religiosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies conducted in the Dominican Republic found that diabetes-related stress begins at diagnosis and persists throughout the self-management process [13]. Furthermore, people with T2D reported that they often experienced a significant emotional burden as a result of their T2D; however, they lacked sufficient emotional support to cope with this emotional burden [13,17,18].…”
Section: Study Settingmentioning
confidence: 99%
“…Participants' mean age was 52 and they had worked at the clinic for a range of 1-8 years. Informed by our past research in this setting [13,17,18], we wrote the interview guide in Spanish and organized it according to the study's three main topics: 1) how providers described the emotional burden of diabetes; 2) how they described their role in supporting the emotional health needs of patients; and 3) barriers to integrating emotional support into routine clinical care.…”
Section: Participants and Data Collectionmentioning
confidence: 99%